Diagnostic accuracy of lung and abdominal ultrasound for tuberculosis in a german multicenter cohort of patients with presumed tuberculosis disease - Weber, Stefan F.; Wolf, Peter; Wetzstein, Nils; Küpper-Tetzel, Claus; Vehreschild, Maria; Suárez, Isabelle; Rybniker, Jan; Klingmüller, Angela; Weber, Tim; Güttlein, Maximilian; Tobian, Frank; Köppel, Lisa; et al. (Open Forum Infectious Diseases, 2024)
There is limited evidence on point-of-care ultrasound for tuberculosis (TB), but studies suggest high sensitivity, especially for lung ultrasound (LUS). However, insufficient data are available on specificity of the examination and its generalizability to a broader patient population.Our study aimed to establish accuracy for lung, chest, and abdominal ultrasound, individually and in combination, for TB diagnosis.We conducted a prospective diagnostic accuracy study among consecutive adult out- and inpatients with probable TB in three German referral hospitals. We applied a comprehensive standardized ultrasound protocol. TB diagnosis was established by a microbiological reference standard including polymerase chain reaction and culture.A total of 102 participants originating from 30 different countries were enrolled. HIV prevalence was 7/99 (7%) and 73/102 (72%) had confirmed TB. TB was limited to the lungs in 15/34 (44%) of refugees and 27/39 (69%) in nonrefugees. Focused assessment with sonography for HIV-associated tuberculosis had a sensitivity of 40% (95% confidence interval [CI], 30-52) and specificity of 55% (95% CI, 38-72). Additional findings, such as small subpleural consolidations on LUS had a high sensitivity (88%; 95% CI, 78-93), but a low specificity (17%; 95% CI, 8-35). Larger consolidations in the lung apices had a sensitivity of 19% (95% CI, 12-30) and a specificity of 97% (95% CI, 83-100).Our study establishes the first data on LUS performance against a comprehensive reference standard. Overall, our data suggest that ultrasound does not meet the requirements for triage but previously described and novel ultrasound targets in combination could aid in the clinical decision making.Registry: DRKS00026636Tuberculosis (TB) is a serious lung disease. Using ultrasound to diagnose TB shows promise, especially for the lungs, but more information is needed about its accuracy. To use of lung ultrasound for triage, it would need to correctly identify at least 90% of persons with TB and not be falsely positive in more than 30% of persons without TB.Our study aimed to determine how well lung, chest, and abdominal ultrasounds could predict TB. We examined adults who might have TB at three hospitals in Germany, using a thorough ultrasound method and confirmed TB diagnoses with culture or polymerase chain reaction.We studied 102 participants from 30 countries, with 7% having HIV. TB was confirmed in 72% of the participants. The focused assessment with sonography for HIV-associated tuberculosis method for HIV-associated TB had a 40% chance of correctly identifying TB and a 55% chance of correctly identifying those without TB. Small lung abnormalities seen on ultrasound had high sensitivity (88%) but low specificity (17%). Larger abnormalities in the top part of the lungs had low sensitivity (19%) but high specificity (97%).In conclusion, lung ultrasound alone does not meet the set expectations for a test to diagnose TB or triage patients for further testing. Nonetheless, combining different ultrasound findings could help doctors make better decisions about TB diagnosis.